REKONTRUKSI PEMIKIRAN HIDDEN CURRICULUM UNTUK MENGINTERNALISASIKAN NILAI-NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PAI - Ikhsan Nur Fahmi (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
Diversity for indonesians is believed to be destiny. Not asked, but rather a gift of God, not to be bargained but to be received (taken for granted). However, there are still certain people or groups who misunderstood the meaning of diversity, triggering conflicts between tribes, religions, races and factions. Education has an important role to prevent horizontal confucianism due to ethnic, racial, and religious differences occurring, namely by internalizing the values of religious moderation through education, PAI becomes a tool to internalize moderate, tolerant, and compassionate religious moderation values to others. The process of internalizing religious moderation values can be done by using hidden curriculum, the term hidden curriculum points to everything that can have an effect in the ongoing teaching and education process that may be able to improve or encourage or even undermine the efforts of achieving educational goals. In other words, hidden curriculum refers to educational practices and results that are not outlined in the programmatic curriculum or the education institution's policy curriculum instructions. This article will analyze and explore internalization models of religious moderation values through hidden curriculum in PAI learning.